2018
DOI: 10.1080/21623945.2018.1453769
|View full text |Cite
|
Sign up to set email alerts
|

What activates thermogenesis when lipid droplet lipolysis is absent in brown adipocytes?

Abstract: Cold exposure activates the sympathetic nervous system. It is generally thought that this sympathetic activation induces heat production by stimulating lipolysis of cytosolic lipid droplets (LDs) in brown adipocytes. However, this concept was not examined in vivo due to lack of appropriate animal models. Recently, we and others have demonstrated that LD lipolysis in brown adipocytes is not required for cold-induced nonshivering thermogenesis. Our studies uncovered an essential role of white adipose tissue (WAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Moreover, mice treated with Atglistatin display higher UCP1 levels in adipose tissue (Schweiger et al 2017). Similarly, deletion of CGI-58 in brown adipose tissue, which partially blocks lipolysis, does not block energy dissipation by adipocytes in mice fed ad libitum (Shin et al 2017(Shin et al , 2018. Mice deficient for ERK3 show about 50% reduced Atgl expression, and at the same time, increased Ucp1 expression in white as well as in brown adipose tissue when fed HFD.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, mice treated with Atglistatin display higher UCP1 levels in adipose tissue (Schweiger et al 2017). Similarly, deletion of CGI-58 in brown adipose tissue, which partially blocks lipolysis, does not block energy dissipation by adipocytes in mice fed ad libitum (Shin et al 2017(Shin et al , 2018. Mice deficient for ERK3 show about 50% reduced Atgl expression, and at the same time, increased Ucp1 expression in white as well as in brown adipose tissue when fed HFD.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of smaller lipid droplets in the BAT from mice lacking HuR is interesting and suggestive of a possible fuel shortage mechanism in BAT from Adipo-HuR −/mice. However, it has been shown that lipolysis of lipid droplets within BAT is not required for thermogenesis [34] and, more recently, that lipid droplets within BAT are entirely dispensable for cold-induced thermogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that food consumption could compensate for thermogenic fuel depletion during cold exposure (40,41), especially during the light phase (11,42). Thus, to avoid any confounding effect of feeding, mice were housed at 4°C for 1 wk with ad libitum access to food, then maintained in the cold environment under fasting conditions for 6 h, beginning at ZT1.…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%